Gender Relations in Stone-Breaking Women’s Families in Southeast Sulawesi, Indonesia: A Phenomenological Study - Hos, Jamaluddin; Arsyad, Muhammad; Bauto, La Ode Monto; Roslan, Suharty; Ridwan, Harnina; Larisu, Zulfiah; Hasniah (Journal of Population and Social Studies [JPSS], 2021)
Low socioeconomic levels of families within the Southeast Sulawesi province of Indonesia encourage women to take on the burden of dual roles. In addition to being a stay-at-home spouse, women also have to work outside the home to help the family financially. Often, based on the experience of women, the work is beyond traditional Indonesian gender roles. The study aims to illustrate the experiences of stone-breaking women who perform these dual roles. This study employed a qualitative method with a phenomenological approach. Data collection using in-depth interviews were conducted with thirteen women who were both homemakers and worked outside the home as stone breakers. The in-depth analysis of interview transcripts yielded six prominent themes: dual roles, economic governance, cooperation, empathy for the couple, caring for education, and husband representation. The six themes described egalitarian and gender representation in partner relationships characterized by the collaboration between men and women in the domestic and public areas of daily life. This relationship created the sincerity of sharing the workload with partners and accepting varying roles without conflict. Furthermore, the tangible economic contribution in fulfilling basic family needs has given the same authority to both husband and wife in the familial decision-making process.